Penentuan Piawaian Alkohol Dalam Makanan Yang Dibenarkan Dari Perspektif Islam - Ab Ghani, Anisah; Ismail, Muhammad Safiri (Jurnal Fiqh, 2010)
The issue of alcohol used in food is still a polemic in the Muslim community because of the perception that alcohol is khamr (alcoholic beverage). This perception is not actually accurate because alcohol and khamr are different. This article discusses the issue of foods containing alcohol, which cannot be evaluated based solely on the percentage of alcohol content, but must also be based on the extent of its capasity to cause intoxication or harm. The rate of the 0.01% alcohol content standard set by JAKIM also needs to be reviewed as it is not considered to be practical or realistic for most of the halal fermented food market, which contains up to 5% alcohol. From the medical perspective, the potential for drunkenness in someone is also affected by the alcohol concentration, the rate of consumption, body weight, gender, age and alcohol consumption with food or on its own.